Supplementary material for “Role of Tad Pili during the transition from Planktonic to Biofilm State in Bradyrhizobium diazoefficiens USDA 110” - Iglesias, Julián (2025)
Free-living soil bacteria can exist in two main states: planktonic, as motile single cells, or sessile, within biofilms. In biofilms, bacterial cells are embedded in an extracellular matrix that provides protection from environmental stresses and enhances long-term survival. The transition from planktonic to biofilm states sometimes involves surface sensing and attachment, processes com-monly mediated by flagella and pili. In this study, we investigated the role of Type IVc Tad pili in surface sensing, adhesion, and biofilm formation in Bradyrhizobium diazoefficiens, a nitrogen-fixing symbiont of soybean. Bioinformatic analyses revealed that Tad pili are widely distributed and high-ly conserved within the Bradyrhizobium genus. While pili deletion in other model organisms typi-cally reduces biofilm formation, we found that deletion of the most conserved genomic cluster encoding Tad pili in B. diazoefficiens led to increased adhesion to abiotic surfaces and impaired motility—indicative of a physiological shift toward a biofilm-associated state. These findings sug-gest that Tad pili may play a sensory or regulatory role, potentially influencing cell-cell or cell-matrix interactions. Furthermore, we identified a link between Tad pili and intracellular c-di-GMP levels. Together, these results highlight the critical role of Tad pili in the physiology of B. diazoeffi-ciens and offer new insights into bacterial surface adaptation, with potential applications in agri-culture and biotechnology. Understanding these mechanisms is essential for improving biofilm management strategies and developing new approaches to enhance bacterial survival in soil and inoculant formulations, ultimately optimizing legume symbiosis.